HAIKU BERTEMAKAN MUSIM DINGIN DALAM BUKU JAPANESE ART AND POETRY (SEBUAH KAJIAN SEMIOTIK) - Indriawan, Patria Restu; Hastuti, Nur; Fadli, Zaki Ainul (Japanese Literature, 2016)
Poetry usually contains the expression of feeling and criticism poet of social life and society in a certain era. Every word in the poem implies that the author’s expression so that the meaning contained in the poem needs to be analyzed to determine the content of the poem. Furthermore in choosing the choice of words (diction) must be precise so that the meaning and the imagine was pointed. In poetry usually tucked the message author to the reader (moral message). One method that can be used in analyzing poetry is to use the symbol analysis, heuristic, and hermeneutic. Symbol analysis is divided into three, namely blank symbol, natural symbol, and private symbol. Blank symbol is a word that expresses certain symbol whose meaning is universal reference so that reader had no trouble interpreting. Natural symbol are words that reveal the reality of nature as a symbol of life projections. Private symbol are words that reveal the symbol specially created and used the poet to express uniqueness. Heuristic is based on the reading of linguistic or semiotic structure is based on the first level convention semiotic system (naturalized poetic language into ordinary language). Meanwhile, hermeneutic means reading poetry at the second level of language (the meaning of the poetry uses literary). The poetry that will be analyzed is haiku (Japanese poem with seventeen syllable with a 5-7-5 pattern) in the Japanese Art and Poetry book. Selected poetry is poetry with the theme of winter. While the result is there are seven blank symbol, seven natural symbol, and two private symbol. Meanwhile, heuristic and hermeneutic majority describe sadness, loneliness, and suffering the author at the time of this haiku made (Edo era).